INNOVATIVE TEACHING METHODS IN TEACHING FOREIGN LANGUAGES AND THE PRINCIPLES OF THEIR APPLICATION IN PRACTICE - Igamova Dildora Nazirovna (Scholar Express Journals, 2022)
This article covers the importance of modern methods and their wide use in order to perfectly teach and learn foreign languages in our country
Keywords: Foreign language; innovative technology; technological tool; modern techniques